JOHN RAWLS’ THEORY OF DISTRIBUTIVE JUSTICE AND CHIEFTAINCY TUSSLES IN TAKUM LOCAL GOVERNMENT AREA OF TARABA STATE 1996-2023 - BAKO KEFAS; SAMUILA TIBWA ABWAGE; BONIFACE TIIVH STEPHEN (International Studies Journal)
This study is a contribution to knowledge on the existence of succession tussles within the Takum traditional council. The study focused on the dynamics of the tussle and was anchored on John Rawls’ Theory of Distributive Justice. This paper adopted expos facto research design and gathered data through secondary sources like, books, journals articles, manuscripts, internet materials, conference papers etc, content analysis was used to analyse data gathered. The study found that the genesis of the problem was colonial interference in the districts through the forceful amalgamation of 1914 of the Takum district and the Zumperi district and the subsequent disrobement of Yamusa Galumje and his replacement with Ukwe Ahmadu Kuffang. The paper recommends that the government should immediately take actions that will facilitate the occupation of the vacant stool and the good people of Takum must be ready to embrace the sharing formula that will capture the interest of both kuteb, Jukun , Chamba other ethnic nationalities that sojourned in Takum for the sake of peace and distributive Justice.